Barley TAPETAL DEVELOPMENT and FUNCTION1 (HvTDF1) gene reveals conserved and unique roles in controlling anther tapetum development in dicot and monocot plants - Hua, Miaoyuan (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.